REKOMENDASI BENGKEL SEPEDA MOTOR TERBAIK DIKOTA MEDAN BERDASARKAN SURVEY KEPUASAN PELANGGAN DENGAN METODE WEIGHTED SUM MODEL (WSM) BERBASIS GIS - Febri Wijaya Hutagalung; Alfonsus Situmorang; Jimmy F. Naibaho (Universitas Methodist Indonesia, 2020)
The rapid growth of the number of vehicles in the city of Medan is increasing, the growth in the number of vehicles (motorcycles) is proportional to the increase in the number of workshops, both official workshops (official dealers) and unofficial workshops that serve vehicle repairs and sell vehicle spare parts. With the many locations of motorcycle repair shops in the city of Medan, sometimes it makes workshop service users feel confused to find the best workshop location according to the desired criteria. This will cause problems for motorcycle repair service users because not all of them know the name of the workshop and its address, especially for service users who live outside the city of Medan. The purpose of this research is to create a Decision Support System to help repair shop service users make the right decisions. The right method to make it easier for users to choose a motorcycle repair shop is to use the method Weighted Sum Model (WSM) with the help of Google Map. By applying the Weighted Sum model method, the system built will provide recommendations for the best motorcycle repair shops to potential users of repair services by displaying the location geographically using a Google Map.